A new approach for predicting solar radiation in tropical environment using satellite images - Case study of Malaysia - Ayu Wazira, Azhari; Kamaruzzaman, Sopian; Azami, Zaharim; AL Ghoul, Mohamad (World Scientific and Engineering Academy and Society (WSEAS) Press, 2009)
Link to publisher's homepage at http://www.wseas.org/